ACUTE KIDNEY INJURY IN HOSPITALIZED COVID-19 PATIENTS: A RETROSPECTIVE OBSERVATIONAL STUDY - Mohammad Asim; Alam, Sartaj; Shakireen, Najmush; Saeed, Rabia; Rahat Ullah, Arslan; ul Abideen, Zain (Journal of Ayub Medical College Abbottabad, 2022)
Background: Published studies have reported that acute kidney injury (AKI) and other kidney related manifestations are associated with COVID-19 and linked with poor outcome. This study aimed to determine the incidence, risk factors and outcomes of AKI in hospitalized COVID-19 patients. Methods: This retrospective study of 154 patients involved retrieving data from hospital records confirm COVID-19 infection admitted to the Northwest General Hospital & Research Center, Peshawar from 1st April to 31st July 2020. AKI was defined using Kidney disease. Improving Global Outcomes (KDIGO) guidelines. Results: Incidence of AKI was 37.01%. Age, gender, intensive care (ICU) requirement, number of co-morbid, diabetes mellitus, coronary artery disease, chronic kidney disease, chronic obstructive airway disease (COAD), arrhythmias among comorbid and fever and shortness of breath among symptoms were found to be significantly differed between AKI and non-AKI patients. Numerous differences of laboratory results such as serum sodium, potassium, total leukocyte count, absolute lymphocyte count and platelets between both groups were observed (p<0.05). Inflammatory markers including lactate dehydrogenase (LDH), ferritin, d-dimer and C-reactive protein (CRP) were significantly raised in AKI group. Overall mortality was observed to be 38 (24.7%). Moreover, age, ICU requirement; COAD, creatinine, serum sodium, inflammatory markers (LDH, ferritin, d-dimers and CRP), total leukocyte count, absolute lymphocyte count, platelets and support requirement were significantly differed between survivors and non-survivors. Mortality was significantly higher among AKI group, i.e., 52.6% compared to 8.2% in non-AKI group (p<0.001). Conclusion: AKI is common among hospitalized COVID-19 patients and is associated with mortality. In all, AKI patients less than half of the patients survived.